Identifikasi Divisi Pteridophyta di Kawasan Danau Aur Kabupaten Musi Rawas - Reny Dwi Riastuti; Sepriyaningsih Sepriyaningsih; Devi Ernawati (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
This study aims to identify the Pteridophyta Division in the Lake Aur Area of ​​Musi Rawas Regency. The research method used is descriptive qualitative. This research was made in 3 plots with size 10 m x 10 m. Based on the result of identification research of Pteridophyta division in Aur Aurland area there are 5 orders, 9 families, 12 genus and 19 species Pteris biaurita, Ploecnemia irregular, Diplazium esculentum, Asplenium nidus, Gleichenia linearis, Christella dentata, Stenochlaena palastris, Diplazium esculentum, Davallia denticulata, Gleichenia linearis, Lygodium scandens, Lygodium circinatum, Nephrolepis exaltata, Nephrolepis cordifoli, Nephrolepis biserrata, Phymatosorus scolopendria, Selaginella wildenowii , Selaginella caudata and Selaginella plana with soil temperature in Aur Aur Area Musi Rawas Regency ranges 27,5˚C-31,5˚C with degree of acidity (pH) of land ranged from 5,11-6,18. Keywords: pteridophya division, aur lake.